Hydrothermal synthesis of Co3O4 nanoparticles decorated three dimensional MoS2 nanoflower for exceptionally stable supercapacitor electrode with improved capacitive performance. (March 2022) - Ahmad, Md. Hasive; Alam, Rabeya Binta; Ul-hamid, Anwar; Farhad, S.F.U.; Islam, Muhammad Rakibul
Highlights: Novel Co3 O4 nanoparticle decorated MoS2 nanoflower (MoS2 /Co3 O4 ) has been fabricated via a facile hydrothermal method. (MoS2 /Co3 O4 ) exhibit specific capacitance as high as 220.72 mFcm -2 at 0.14 mAcm -2 . Superior cycling stability, 87% capacitance retention after 10, 000 charge/discharge cycles was obtained. Abstract: In this study, a novel, Co3 O4 nanoparticle decorated MoS2 nanoflower (MoS2 /Co3 O4 ) has been fabricated via a facile hydrothermal method by taking different concentrations of Co3 O4 (0, 1, 2, 4, and 6%). The FE-SEM images represent a three-dimensional flower-like structure for MoS2 and MoS2 /Co3 O4 . The different structural parameters of the nanoflowers were estimated from the XRD analysis. TEM analysis revealed that the inter-planar spacing of the nanostructure varied with the concentration of the Co3 O4 nanoparticles. The Raman spectroscopy of MoS2 /Co3 O4 nanoflower showed a distinct low-shift of the first-order Raman peaks suggesting n-type doping due to the incorporation of Co3 O4 . The specific capacitance as high as 220.72 mFcm -2 at 0.14 mAcm -2 together with high energy density and superior cycling stability (87% capacitance retention after 10, 000 charge/discharge cycles) were obtained for the MoS2 /Co3 O4 (4%) nanocomposite from the electrochemical analysis. This improved specific capacitance of MoS2 /Co3 O4 can be attributed to the higher surface area, defect-rich structure, and lower charge transfer resistance of the prepared sample. The MoS2 /Co3 O4 nanostructure with improved specific capacitance and higher stability synthesized from a simple, low-cost process will pave the way to the production of efficient and economic energy storage devices.